2001
DOI: 10.1074/jbc.m100621200
|View full text |Cite
|
Sign up to set email alerts
|

Two Active Molecular Phenotypes of the Tachykinin NK1 Receptor Revealed by G-protein Fusions and Mutagenesis

Abstract: The NK1 neurokinin receptor presents two non-ideal binding phenomena, two-component binding curves for all agonists and significant differences between agonist affinity determined by homologous versus heterologous competition binding. Whole cell binding with fusion proteins constructed between either G␣ s or G␣ q and the NK1 receptor with a truncated tail, which secured nonpromiscuous G-protein interaction, demonstrated monocomponent agonist binding closely corresponding to either of the two affinity states fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 41 publications
4
76
0
Order By: Relevance
“…Thus, in the NK1 receptor, mutation of PheIII:07 (Phe 111 ) selectively decouples the receptor from G s without affecting G␣ q signaling (18). For the angiotensin receptor it has been shown that Ala substitution of ProII:18 in the AT1 receptor completely impairs angiotensin II signaling through G␣ q without affecting high affinity binding of the peptide agonist and the ability of angiotensin II to stimulate ERK phosphorylation (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the NK1 receptor, mutation of PheIII:07 (Phe 111 ) selectively decouples the receptor from G s without affecting G␣ q signaling (18). For the angiotensin receptor it has been shown that Ala substitution of ProII:18 in the AT1 receptor completely impairs angiotensin II signaling through G␣ q without affecting high affinity binding of the peptide agonist and the ability of angiotensin II to stimulate ERK phosphorylation (53).…”
Section: Discussionmentioning
confidence: 99%
“…able to modulate energy expenditure and food intake without affecting growth hormone secretion or vice versa. The structural understanding of biased signaling has been addressed only to a limited degree, and information is primarily based on mutations that selectively decouple one signaling pathway and not the other (18,19).…”
mentioning
confidence: 99%
“…An increased concentration of cAMP activates the protein kinase A (PKA), which phosphorylates specific substrates (86). Finally, coupling with Gαi inhibits AC, which, thereafter, decreases the concentration of cAMP in the cell (87,88).…”
Section: The Substance P/neurokinin-1 Receptormentioning
confidence: 99%
“…two distinct functional states, which might then interact with different G proteins (reviewed in Nusbaum and Blitz, 2012). Similar reports of multiple states for neurokinin (Holst et al, 2001;Palanche et al, 2001;Sachon et al, 2002) and muscarinic (Gurwitz et al, 1994) receptors from mammals, as well as for aminergic receptors from Drosophila (Reale et al, 1997;Robb et al, 1994), have likewise been reported.…”
Section: Pyrokinins Activate the Gastric Mill But Not The Pyloric Motmentioning
confidence: 64%